Reinforced Oil Palm Fiber Epoxy Composites: An Investigation on Chemical Treatment of Fibers on Acoustical, Morphological, Mechanical and Spectral Properties - Bakri, M.K.B.; Jayamani, E.; Heng, S.K.; Sinin, Hamdan (Elsevier Ltd, 2015)
Oil palm fibers are plentifully unused waste types of cellulose fibers. It is extensively being wasted in modern agriculture and industries because of the limited research and knowledge on the use and functionality of oil palm fibers in certain sectors and products. Throughout this research, studies and examinations conducted to investigate the developments of reinforced untreated and treated oil palm fiber epoxy composites. Then, the effects of alkaline treatment on the fiber structure being analyzed. Lastly, based on the results obtained, the effects on the acoustical, morphological, mechanical, and spectral properties being investigated according to specific tests and standards.